2019
DOI: 10.1002/bdr2.1445
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of infants born to women with influenza A(H1N1)pdm09

Abstract: Background: Pregnant women with influenza are more likely to have complications, but information on infant outcomes is limited. Methods: Five state/local health departments collected data on outcomes of infants born to pregnant women with 2009 H1N1 influenza reported to the Centers for Disease Control and Prevention from April to December 2009. Collaborating sites linked information on pregnant women with confirmed 2009 H1N1 influenza, many who were severely ill, to their infants’ birth certificates. Collabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 19 publications
(34 reference statements)
0
27
0
Order By: Relevance
“…While we did not record placental and fetal weights, it is likely that a similar growth retardation is present in our model considering the substantial body weight reduction in pregnant dams after correcting for litter size. Indeed, rates of intrauterine growth restriction leading to lower birth weight infants are increased following gestational IAV infection in humans 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we did not record placental and fetal weights, it is likely that a similar growth retardation is present in our model considering the substantial body weight reduction in pregnant dams after correcting for litter size. Indeed, rates of intrauterine growth restriction leading to lower birth weight infants are increased following gestational IAV infection in humans 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the lack of transcriptional changes in immune, barrier integrity, and neurodevelopmental genes here suggests that offspring neurological outcomes, if present, are likely to be more mild than what has previously been described in the H1N1 A/NWS/33 infection model [65][66][67][68] . Indeed, recent epidemiological data indicates that severe IAV infection during pregnancy significantly elevated the risk of adverse infant outcomes, while less severe infection did not 52 . Our data support a model in which a moderately pathogenic IAV infection is below the severity threshold necessary to induce detrimental effects on fetal brain immune equilibirum.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been shown that children under 6 months of age usually only develop a fever but are very likely to be hospitalized with a favorable outcome in most cases, as described by Bender et al 13 Most published articles insist and conclude that influenza rates in infants can be reduced by adopting a cocoon strategy that involves vaccinating close contacts and mothers during pregnancy and even during lactation for those not previously vaccinated. [14][15][16][17][18][19][20][21] It is necessary to promote and stimulate vaccination in all pregnant women, 22 which, in Spain, barely reaches 50% coverage in the best scenario. López-Medina et al 23 showed that during the 2009 pandemic, most Spanish newborns developed a community-acquired influenza infection, which was found to be associated with hospital admissions and favorable short-term results.…”
Section: Discussionmentioning
confidence: 99%
“…Infants born to mothers who were vaccinated against influenza may have a decreased rate of preterm birth, low birthweight, and stillborn birth, although establishing a causal relationship is challenging [160,[166][167][168][169][170][171]. Infants born to mothers who were severely sick with H1N1 influenza infection have been shown to have an increased risk of preterm birth, decreased 5 min Apgar scores, and an increased risk of death [172][173][174]. These data support vaccinating pregnant women to help improve the health of both the mother and child.…”
Section: A Key Role For Maternal Vaccination In Protecting Young Infamentioning
confidence: 99%